Profil Kemampuan Technological Pedagogical Content Knowledge (TPACK) Guru Kimia SMA di Kalimantan Barat - Erlina Erlina; Maria Ulfah (Hydrogen: Jurnal Kependidikan Kimia, 2022)
This study aims to determine the level of technological pedagogical content knowledge (TPACK) of High School Chemistry teachers. The method used is descriptive quantitative method. The participants involved in this study were 42 high school chemistry teachers from 42 different schools in Kalimantan Barat. The instrument used in this study is a questionnaire adapted from the TPACK Assessment developed by Schmidt, Baran, Thompson, Mishra, Koehler & Shin (2009) with 5 answer options with a Likert scale. Based on data analysis, the average TPACK ability score in each aspect is: for the TK aspect 75.03 with a good category; the average score on the CK aspect is 72.82 in the good category; the average score for the PK aspect; 76.12 in the good category; PCK aspect; 72.62 also in the good category; the TCK aspect; 71.43 in the good categor; in the TPK aspect; 75.71 in the good category; and in the last aspect, TPACK; an average score of 72.48 was obtained which is in the good category. Based on these findings, it can be concluded that chemistry teachers in Kalimantan Barat have a good TPACK abilities, thus those teachers properly use the technology in the teaching process. The range of correlation data shows a strong and very strong relationship with a positive correlation coefficient ranging from 0.691-0.931. This shows a significant correlation for each aspect of TPACK.